Simple and Rapid Detection of Factor V Leiden by Allele-specific PCR Amplification - Blasczyk, Rainer; Ritter, Markus; Thiede, Christian; Wehling, Jenny; Hintz, Günter; Neubauer, Andreas; Riess, Hanno (Thrombosis and Haemostasis, 1996)
Resistance to activated protein C is the most common hereditary cause for thrombosis and significantly linked to factor V Leiden. In this study, primers were designed to identify the factor V mutation by allele-specific PCR amplification. 126 patients with thromboembolic events were analysed using this technique, PCR-RFLP and direct sequencing. The concordance between these techniques was 100%. In 27 patients a heterozygous factor VGln506 mutation was detected, whereas one patient with recurrent thromboembolism was homozygous for the point mutation. Due to its time- and cost-saving features allele-specific amplification should be considered for screening of factor VGln506.